((C))
Line 24: Line 24:
 
== (C) ==
 
== (C) ==
  
I'm not sure what to do here though
+
Just factor the top of the equation like this: (e^(-2t) - 1) into (e^(-t) + 1)*(e^(-t) - 1)
 +
 
 +
Then you can cancel some terms and there you go.
  
 
[[User:Idryg|Idryg]] 21:02, 6 October 2008 (UTC)
 
[[User:Idryg|Idryg]] 21:02, 6 October 2008 (UTC)

Revision as of 17:13, 6 October 2008

(A)

So you know:

A(t) = the integral of e^(-x) dx from 0 to t

and

V(t) = the integral of Pi*[e^(-x)]^2 dx from 0 to t

Just evaluate the integrals:

A(t) = -e^-t + 1

and

V(t) = -(1/2)*Pi*e^-2x + Pi/2

and then take the limits as t approaches infinity.

(B)

Just put V(t) over A(t) and take the limits.

(C)

Just factor the top of the equation like this: (e^(-2t) - 1) into (e^(-t) + 1)*(e^(-t) - 1)

Then you can cancel some terms and there you go.

Idryg 21:02, 6 October 2008 (UTC)

On part C, since e^a is valid for all real a, and since V(0) and A(0) are valid functions (i.e. V(0) does not give a no solution), the limit as t approaches zero from the right is the same as if t approaches infinity from the left. This means that you can just take the limit as t approaches 0 and ignore the 0+ aspect of the problem. I am not %100 sure about this, but this is how I understood the problem, maybe if someone graphs this, we can see what V(t)/A(t) is approaching when t = 0. --Ctuchek 21:13, 6 October 2008 (UTC)

Alumni Liaison

Ph.D. 2007, working on developing cool imaging technologies for digital cameras, camera phones, and video surveillance cameras.

Buyue Zhang